Intein-mediated split SaCas9 for genome editing in plants - Hu, Danling; Hu, Lizhe; Lu, Yaqiang; Dong, Xiao; Cao, Xingyu; Bai, Shasha; Zhang, Lingang; Li, Dongming; Sun, Yongwei (Frontiers in Genome Editing, 2025)
Virus-induced genome editing (VIGE) technologies have been developed to address the limitations to plant genome editing, which heavily relies on genetic transformation and regeneration. However, the application of VIGE in plants is hampered by the challenge posed by the size of the commonly used gene editing nucleases, Cas9 and Cas12a. To overcome this challenge, we employed intein-mediated protein splicing to divide the SaCas9 transcript into two segments (Split-v1) and three segments (Split-v3). The Split-v1 system demonstrated genome editing efficiencies in transgenic plants comparable to those achieved with wild-type SaCas9, with efficiencies ranging from 70.2% to 96.1%. Additionally, we constructed barley stripe mosaic virus (BSMV)-based vectors to co-express Split-v1 SaCas9 and gRNAs targeting LcHRC, LcGW2, and LcTB1 in sheepgrass (Leymus chinensis), a Gramineae forage species known for its recalcitrance to genetic transformation. Infected leaves of sheepgrass exhibited genome editing efficiencies ranging from 10.40% to 37.03%. These results demonstrate the potential of intein-mediated split nuclease systems to broaden the applicability of VIGE in challenging plant species.